Helping Turkish EFL learners with the pronunciation of four general British vowels - Şen, Serkan (ELOPE (Ljubljana), 2019)
The article presents and discusses a mixed-method study that aimed at establishing how pre-service teachers of English as a Foreign Language (EFL) self-assessed those sounds of the English language that would cause problems for their pronunciation in EFL. Fourteen pre-service EFL teachers on the intermediate level of EFL proficiency whose first language (L1) was Norwegian were recruited for the study. They were asked to write reflective essays concerning the sounds of the English language that they considered problematic to pronounce. The participants' essays were contrasted with the essays written by the control group that was comprised of 14 in-service EFL teachers whose L1 was Norwegian. The results of the analysis revealed that the participants identified several English sounds that they self-assessed as problematic to pronounce, e.g. /z/, /%/, /%/, and /%/. The analysis of the controls' essays yielded similar results. These findings and their linguo-didactic implications are discussed in the article.
Keywords: angleška izgovarjava; ortografija; samoglasniški sistem; standardni angleški samoglasniki; turščina